Urban design and adolescent mental health: A qualitative examination of adolescent emotional responses to pedestrian- and transit-oriented design and cognitive architecture concepts. (July 2022) - Buttazzoni, Adrian; Dean, Jennifer; Minaker, Leia
Abstract: With the continued migration of people into cities, urban environments are becoming increasingly important determinants of health. However, the study of how precise environmental designs are linked to mental health are generally lacking, especially among adolescent populations. Using a qualitative approach featuring 23 go-along interviews with adolescents, we investigated the relationships between specific urban designs as outlined in pedestrian- and transit-oriented design (imageability, enclosure, scale, transparency, complexity) and cognitive architecture (biophilic architecture, symmetries, fractals) concepts and adolescent mental health indicators (i.e., emotional responses). Central findings from the subsequently undertaken framework analysis include considerably different perceptions regarding natural versus built enclosure and landmarks, significantly more expressed emotional engagement with visually rich and transparent urban designs relative to grey/concrete and windowless designs, and strong positive reactions to the three cognitive architecture concepts. Additional exploratory gender-based analyses were conducted and found potential differences in perceptions of design concepts between boys and girls. We note the broader relevance of these findings by discussing their implications for practitioners and suggesting how they can advance certain UN Sustainable Development Goals. Highlights: Links between adolescent mental health and eight designs concepts were explored. Qualitative methods including 23 go-along interviews, framework analysis was used. Positive emotional links noted for visual richness, transparency, natural enclosure. Negative emotions tied to lack of human scale, artificial noise, minimal complexity. Possible gender-specific links were noted for girls and scale, transparency designs.